2020
DOI: 10.1007/s00192-020-04345-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood nocturnal enuresis—a marker for pelvic floor disorders and urinary tract symptoms in women?

Abstract: Introduction and hypothesis A systematic survey on the association between childhood nocturnal enuresis (CNE) and adult pelvic floor disorders (PFDs) has not been presented previously. The aim was to describe the prevalence of PFDs and lower urinary tract symptoms in nulliparous women, with or without a history of CNE, at the age of ≥ 5 years. Methods This national survey of urinary (UI) and fecal incontinence (FI) and symptoms of pelvic organ prolapse (sPOP) was a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The authors concluded that childhood symptoms as nocturia and nocturnal enuresis were strongly associated with symptoms in middle‐aged and older women. An internet‐based questionnaire survey conducted by Othman et al 35 described the prevalence of nocturia ≥2 was higher in women with a history of childhood enuresis. However, this study was based only on the female population.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that childhood symptoms as nocturia and nocturnal enuresis were strongly associated with symptoms in middle‐aged and older women. An internet‐based questionnaire survey conducted by Othman et al 35 described the prevalence of nocturia ≥2 was higher in women with a history of childhood enuresis. However, this study was based only on the female population.…”
Section: Discussionmentioning
confidence: 99%
“…Most ORs of the individual studies ranged between 1.00 and 2.00. 23 , 25 , 27–29 Specifically, studies 1, 5, 6, and 7 showed statistically significant associations between the two conditions (OR: 2.38, CI: 1.94–2.94; OR: 1.39, CI: 1.20–1.57; OR: 1.91, CI: 1.53–2.38; OR: 3.75, CI: 2.55–5.52; respectively). 22 , 25 , 26 , 28 Overall, the pooled random effects model also showed a significant association between NE and nocturia (OR: 1.75, CI: 1.11–2.40).…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 25 , 27–29 Specifically, studies 1, 5, 6, and 7 showed statistically significant associations between the two conditions (OR: 2.38, CI: 1.94–2.94; OR: 1.39, CI: 1.20–1.57; OR: 1.91, CI: 1.53–2.38; OR: 3.75, CI: 2.55–5.52; respectively). 22 , 25 , 26 , 28 Overall, the pooled random effects model also showed a significant association between NE and nocturia (OR: 1.75, CI: 1.11–2.40). A pooled random effects model was used in order to take into account both within- and between-study variability when calculating pooled OR estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood dysfunctional voiding may predict adult bladder control problems particularly in women with urge incontinence [12]. Pelvic floor disorders and LUTs are approximately doubled in nulliparous women with a history of childhood bedwetting [13]. Nocturnal enuresis in childhood is predictive of nocturia and frequency in adult women [14].…”
Section: Introductionmentioning
confidence: 99%